Inhibition and Recovery of Acetylcholinesterase Activity in the fish Labeo rohita (Hamilton,1822) following Exposure to Annona squamosa Leaf Extract (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The agricultural sector urgently requires sustainable substitutes for synthetic organophosphate and carbamate pesticides, which pose environmental and health risks due to their irreversible inhibition of acetylcholinesterase (AChE). This study confirms the traditional use of Annona squamosa (Sugar Apple) leaves as a biopesticide by examining their neurotoxic impact on the non-target aquatic species Labeo rohita (Hamilton, 1822). The fish were subjected to a 100 mg/L concentration of fresh Annona squamosa leaf extract for a duration of 96 hours. Following this, a recovery phase was initiated by transferring the fish to clean water for 120 hours. AChE activity in the kidney was periodically measured using the Ellman method, while protein content was determined with the Lowry assay. Exposure to Annona squamosa leaf extract resulted in a significant reduction in AChE activity in the kidney, with a value of 5.93 ± 1.01 nmol/min/mg protein, corresponding to 21.45% inhibition relative to the control group. During the recovery phase, enzymatic activity gradually improved, with 13.58% recovery at 48 hours, 38.88% at 72 hours, 64.81% at 96 hours, and 79.62% after 120 hours in freshwater. These findings demonstrate that Annona squamosa leaf extract exhibits considerable anticholinesterase activity, yet the recovery of inhibited AChE is rapid. This research provides biochemical evidence supporting the integration of Annona species into modern Integrated Pest Management (IPM) strategies as a biodegradable and effective natural alternative to synthetic chemicals.